Numerical investigation of MIL-101(Cr)/GrO composite performance in adsorption cooling systems. (December 2017) - Elsayed, Eman; AL-Dadah, Raya; Mahmoud, Saad; Anderson, Paul; Hassan, Ashraf; Youssef, Peter
Abstract: MIL-101(Cr)/graphene oxide composites were investigated for the application of adsorption cooling. Two composites with two different synthesis techniques were chosen, 2%GrO_syn and 5%GrO_phys, owing to the superior water adsorption uptake of the first and the high thermal conductivity of the latter. The thermodynamic cycle performance of a two-bed adsorption system was evaluated using Simulink software to assess the performance of each composite. Under the operating conditions investigated, the 2%GrO_synthesis composite showed a similar specific cooling power (SCP) and coefficient of performance (COP) to the MIL-101(Cr) system with no change in cycle time and with a lower desorption temperature of 90°C. The 5%GrO_phys composite showed a decreased SCP and an increased COP at the same cycle time. Nevertheless, the desorption temperature of such system decreased from 100°C for the neat material to only 80°C. This highlights the potential of such composites in more efficient adsorption heat pump systems.